The development of real-time control firmware for a wall climbing robot : a small-scale embedded hard real-time system - 560239 Dayang Norhayati (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Master of Science (Computer Science)) - Universiti Teknologi Malaysia, 2000